THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZING SOCIAL MEDIA INTERACTIONS: IMPLICATIONS FOR CONSUMER ENGAGEMENT - Vilma Dewi Anggraeni; Delvin Musa Navarro Matulessy; Kimmy Azizah Sumengkar (PT Altin Riset Publishing, 2026)
This study explores the pivotal role artificial intelligence (AI) plays in shaping personalized experiences on social media, with the aim of deepening user engagement. Drawing from real-world examples, we examine how leading companies like Starbucks, Sephora, and Spotify have embraced AI to tailor content and interactions, with the research is taking place in numerous brands and companies like Starbucks, Sephora, Spotify, and Hilton Hotels & Resorts. the researchs also reaches social media Tiktok and Instagram, as well AI related systems like Llama 2. This research uses Qualitative Research with types of research including Descriptive Studies, Literacy Studies, and Case Studies. Data analysis was carried out using thematic analysis techniques, where the collected data were identified and categorized based on key themes. Websites and apps can use AI to recommend content, products, or services based on the user’s past behaviour or search history.